2010
DOI: 10.21914/anziamj.v51i0.1717
|View full text |Cite
|
Sign up to set email alerts
|

A rational approximation to the evolution of a free surface during fluid withdrawal through a point sink

Abstract: The time varying flow in which fluid is withdrawn from a reservoir through a point sink of variable strength beneath a free surface is considered. Asymptotic techniques are used to derive an approximate solution to the flow that is valid at intermediate times, giving a simple rational approximation to track changes in the free surface for any temporal variations in the sink strength. Comparisons with numerical simulations are given, showing that the approximation has wide applicability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The cases of infinite or finite depth fluid, two-dimensional or three-dimensional and steady or unsteady flows have been considered in single-and multi-layered fluids. The problems of the three-dimensional flow due to a point sink, and the unsteady flow due to a line or point sink have been considered by Hocking et al [10,11], Stokes et al [19][20][21], Xue and Yue [30] and references therein. Of particular interest in this paper is the steady two-dimensional flow due to a line source or sink in a single layer of fluid, for which two main solution types exist.…”
Section: Introductionmentioning
confidence: 99%
“…The cases of infinite or finite depth fluid, two-dimensional or three-dimensional and steady or unsteady flows have been considered in single-and multi-layered fluids. The problems of the three-dimensional flow due to a point sink, and the unsteady flow due to a line or point sink have been considered by Hocking et al [10,11], Stokes et al [19][20][21], Xue and Yue [30] and references therein. Of particular interest in this paper is the steady two-dimensional flow due to a line source or sink in a single layer of fluid, for which two main solution types exist.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the behaviour was found to be qualitatively very similar to the infinite depth line sink case [26]. In [15], Hocking et al showed that a simple rational approximation could be obtained based on the solution to the linearised equations and that this performed well in comparison with the full non-linear solution at small values of the flow rate and if the variation in the flow rate was small. The question arises, given the differences between finite and infinite depth in the two-dimensional flow, whether a similar difference exists in the case of a point sink in axisymmetric flow.…”
Section: Introductionmentioning
confidence: 75%
“…For example, the change in local depth in the two-dimensional finite depth case [28] is well described by a first-order linearised solution. Likewise, in the infinite depth point sink problem [15], a Froude number expansion provided an excellent representation of the development of the free surface as the flow rate was increased and a rational approximation was obtained that performed very well in simulating a variety of subcritical flows. It is therefore worthwhile to consider such solutions here, both for the insight provided and also to verify the numerical scheme.…”
Section: Asymptoticsmentioning
confidence: 99%
See 2 more Smart Citations